Robustness to strategic uncertainty in price competition - Ola Andersson; Cédric Argenton; Jörgen W. Weibull (Stockholm School of Economics, The Economic Research Institute (EFI), 2010)
We model a player's uncertainty about other player's strategy choices as probability distributions over their strategy sets. We call a strategy profile robust to strategic uncertainty if it is the limit, as uncertainty vanishes, of some sequence of strategy profiles in each of which every player's strategy is optimal under his or her uncertainty about the pthers. We apply this definition to Bertrand games with a continuum of equilibrium prices and show that our robustness criterion selects a unique Nash equilibrium price. This selection agrees with available experimental findings.
Keywords: C72; D43; L13; 330; Nash equilibrium; refinement; strategic uncertainty; price competition; Nichtkooperatives Spiel; Unvollkommener Markt; Preiswettbewerb; Nash-Gleichgewicht; Theorie